(untitled) (Islas, 2025)
Introduction: Education is a fundamental human right and a powerful tool for personal and community development. However, indigenous women and girls face significant challenges that hinder their access to the educational system and affect their overall development. Methods: This study proposes awareness-raising actions to support the development of indigenous women and girls in Atliaca, Guerrero, Mexico. Using a qualitative and explanatory approach, their sociocultural and educational context was analyzed. Interviews and surveys were conducted with women, girls, educational authorities, teachers, parents, and community leaders. Descriptive statistical procedures were employed to identify key patterns. Results: Four main aspects were identified: the gender and ethnic gap in access, retention, and educational achievements; the social, cultural, economic, and political factors that limit their right to education; current initiatives to promote their education; and the associated benefits of their educational development. Conclusions: Awareness-raising actions are proposed to highlight the benefits of education, create spaces for dialogue and collaboration, provide guidance and advice, and promote support programs and scholarships. These actions aim to ensure comprehensive development for indigenous women and girls.